1985
DOI: 10.1042/bj2260123
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ethanol, alone and in combination with the glucocorticoids and insulin, on glucose-6-phosphate dehydrogenase synthesis and mRNA in primary cultures of hepatocytes

Abstract: The hormonal regulation of the relative rate of synthesis and mRNA of glucose-6-phosphate dehydrogenase (G6PDH; EC 1.1.1.49) was studied in primary cultures of adult-rat liver parenchymal cells maintained in a chemically defined medium. Maintenance of hepatocytes from starved animals in a culture medium devoid of any hormones resulted in a 4-fold increase in the relative rate of G6PDH synthesis in 48 h. Parallel cultures treated with glucocorticoids alone exhibited a rate of G6PDH synthesis comparable with tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Hormones and cytokines, such as glucocorticoids, TNF‐α and IL‐1, which are increased in plasma of tumor patients, regulate the activity of reducing power generating sites as CS and G6PDH (Stumpo and Kletzien 1985; Rosa et al . 1992; Leff et al .…”
Section: Discussionmentioning
confidence: 99%
“…Hormones and cytokines, such as glucocorticoids, TNF‐α and IL‐1, which are increased in plasma of tumor patients, regulate the activity of reducing power generating sites as CS and G6PDH (Stumpo and Kletzien 1985; Rosa et al . 1992; Leff et al .…”
Section: Discussionmentioning
confidence: 99%
“…For example, oxygen-derived free radicals have been implicated in the pathogenesis of ethanol-induced liver injury (50) and acute ethanol intoxication has been shown to stimulate superoxide anion production in perfused rat liver in situ (51). Earlier studies have demonstrated that ethanol is capable of inducing G6PDH activity, relative rate of G6PDH enzyme synthesis, and mRNA in primary cultures of rat hepatocytes (52). Further studies have shown that acetaldehyde is a likely metabolite mediating the effect of ethanol, with increases in G6PDH mRNA being observed within three hours of incubation (53).…”
Section: Deficiency Of G6pdh In Erythrocytes Renders the Cells Sensitmentioning
confidence: 99%
“…Hepatic G6PD is induced by chemicals such as diquat (Cramer et al, 1993), ethanol (Stumpo and Kletzien, 1985). Studies have revealed that ethanol induces G6PD activity, relative rate of G6PD enzyme synthesis and mRNA in primary cultures of rat hepatocytes (Stumpo and Kletzien, 1985).…”
Section: Regulation Of Glucose-6-phosphate Dehydrogenase By Oxidativementioning
confidence: 99%
“…Hepatic G6PD is induced by chemicals such as diquat (Cramer et al, 1993), ethanol (Stumpo and Kletzien, 1985). Studies have revealed that ethanol induces G6PD activity, relative rate of G6PD enzyme synthesis and mRNA in primary cultures of rat hepatocytes (Stumpo and Kletzien, 1985). The oxidative stress experiments in Trypanosoma cruzi showed that metacyclic trypomastigotes and amastigotes have high G6PD activity (Igoillo-Esteve and Cazzulo, 2006).…”
Section: Regulation Of Glucose-6-phosphate Dehydrogenase By Oxidativementioning
confidence: 99%